Inkjet Printing: Patterning of Nanoparticle‐Based Aerogels and Xerogels by Inkjet Printing (Small 39/2019). Issue 39 (25th September 2019) - Lübkemann, Franziska; Miethe, Jan Frederick; Steinbach, Frank; Rusch, Pascal; Schlosser, Anja; Zámbó, Dániel; Heinemeyer, Thea; Natke, Dominik; Zok, Dorian; Dorfs, Dirk; Bigall, Nadja C.
Abstract : In article number 1902186, Nadja C. Bigall and co‐workers manufacture semiconductor nanoparticle‐based aerogel‐coated electrodes automatically via inkjet printing. By simultaneously printing a destabilization agent and semiconductor nanoparticles, a 3D aerogel‐type network on a conducting and transparent surface is obtained. Furthermore, the charge‐carrier mobility within the 3D aerogel‐type network is investigated via spectro‐electrochemical measurements.